The relationship between infertility family stigma, self-stigma and psychological well-being in female first-visit patients at a reproductive medicine center in Taiwan - Yi-Tung Lin; Ashley W. Wang; Shirley Wei; Jia-Sin Hong; Wen-Yau Hsu (Health Psychology Report, 2021)
Introduction Steeped in Chinese culture which considers continuing the family lineage highly important, infertility stigma endorsed by others and oneself can both negatively impact psychological well-being in women with infertility in Taiwan. The aim of the present study was to find out whether family stigma attached to infertility has a direct effect on psychological well-being, or whether it is only when family stigma is internalized into self-stigma that psychological well-being is affected.